Analysis of the Use of the Term 'Widow' and Its Impact on the Electability of the Rido Candidate Pair in the Jakarta Regional Election Through the Shannon-Weaver Communication Model - Henry T. Sianipar; Fitri Sarasati; Hamzah Ramadhan; Tri Wahyuti (INTERACTION: Jurnal Pendidikan Bahasa, 2024)
The candidates for Governor and Deputy Governor of DKI Jakarta 2024, Ridwan Kamil and Suswono (RIDO), utilized the Shannon-Weaver communication model. The controversy began with Suswono's statement suggesting that "wealthy widows marry unemployed young men," followed by a similar remark from Ridwan Kamil. This study explores how the use of sensitive language can influence public perception and the electability of political candidates. Using the Shannon-Weaver model, the study identifies five stages of communication: information source, encoding process, channel and noise, receiver, and destination. The analysis results reveal that semantic noise and socio-cultural contexts sensitive to gender issues significantly contributed to negative perceptions among the public. Criticism from various organizations and public figures amplified this negative impact, which was reflected in the decline of RIDO's electability, ultimately leading to their defeat in the 2024 Jakarta election. This study highlights the importance of careful word choice in political communication and how semantic noise can affect message effectiveness. The Shannon-Weaver model, although initially designed for technical communication, can be adapted to analyze the complexities of contemporary political communication, particularly regarding the use of language with sensitive gender and social dimensions.